The Influence of Leadership Style, Job Stress, and Job Satisfaction on Employee Turnover Intention Level - Sakti, Sri Handoko; Ikhsan, Muhammad; Pranogyo, Antaiwan Bowo; Abdoellah, M. Natser; Zabidi, Imron (Jurnal Global Ilmiah, 2024)
This study aims to determine how much influence Leadership Style, Job Stress, and Job Satisfaction have on Employee Turnover Intention (Case Study at PT. Freight Cargo Logistics). This study uses an associative research strategy with a quantitative approach. The population in this study were all employees of PT. Freight cargo logistics and there are totaling 42 employees. The method used for sampling is the non-probability sampling technique with the saturated sample technique and the number of samples used in this study is 42 respondents. The data used in this research is primary data. Data collection techniques using questionnaires and observation methods. The data analysis method used is descriptive analysis and inferential analysis using Partial Least Square (PLS) analysis through SmartPLS 3.3.9 software which includes testing the outer model, inner model, and testing the hypothesis. The results of the study prove that partially the variables of Leadership Style and Job Stress have a positive and significant effect on Turnover Intention, while Job Satisfaction has a negative and significant effect on Turnover Intention.